2009
DOI: 10.1111/j.1600-0528.2009.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sense of coherence on the relationship between childhood socioeconomic status and adult oral health‐related behaviours

Abstract: The relationship between childhood SES and adult oral health-related behaviours was mainly mediated by adulthood SES, and to a much less extent by SOC. A stronger SOC was significantly associated with better adult oral health-related behaviours, after controlling for the effect of adulthood SES and demographic characteristics of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 37 publications
6
40
0
3
Order By: Relevance
“…The mean SOC score was lower among those who failed school more often and those who lived with a greater number of people (Table 2). The results presented a positive association between higher SOC and lesser dental caries experience, which is in agreement with data described in previous investigations [15,[22][23][24]. The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The mean SOC score was lower among those who failed school more often and those who lived with a greater number of people (Table 2). The results presented a positive association between higher SOC and lesser dental caries experience, which is in agreement with data described in previous investigations [15,[22][23][24]. The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15].…”
Section: Resultssupporting
confidence: 81%
“…The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15]. Subsequent studies also indicated a high SOC score to be a determinant factor of oral health [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in agreement with previous studies [22][23][24][25] and can demonstrate the impact of financial constraints on the ability of mothers to face and deal with everyday difficulties.…”
Section: Discussionsupporting
confidence: 83%
“…According to Antonovsky,3 SOC is "a global orientation that expresses the extent to which one has a pervasive, enduring though dynamic feeling of confidence that (1) the stimuli from one's internal and external environments in the course of living are structured, predictable, and explicable; (2) the resources are available to one to meet the demands posed by these stimuli; and (3) these demands are challenges, worthy of investment and engagement". 3 The SOC has been shown to be a promising resource for establishing healthy behaviors 4,5,6,7,8,9,10,11,12,13,14,15,16 and a positive self-perception of oral health, 14,16 which increases the interest in investigating its relationship…”
Section: Introductionmentioning
confidence: 99%